2005
DOI: 10.1097/01.pec.0000159074.85808.14
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Emergency Department Assessment and Management of Pain in Children

Abstract: Disparity exists between perceived and documented emergency department pain management practices for children. Quality improvement initiatives should focus on improving pain assessment in infants, treating moderate to severe pain in children of all age groups, and education of health care providers in pain management strategies. Resources should target health care processes effective in decreasing pediatric pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…Patient volume, workload, and competing priorities have been reported to be contributing factors (Byrne & Heyman, 1997;Ellis et al, 2007;Olive, 2003;Probst et al, 2005;Puls-McColl et al, 2001;Smith & Feied, 1999) to the under management of pain. Byrne and Heyman (1997) reported that nurses felt it was more important to move patients through the emergency department.…”
Section: Contextual Influencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Patient volume, workload, and competing priorities have been reported to be contributing factors (Byrne & Heyman, 1997;Ellis et al, 2007;Olive, 2003;Probst et al, 2005;Puls-McColl et al, 2001;Smith & Feied, 1999) to the under management of pain. Byrne and Heyman (1997) reported that nurses felt it was more important to move patients through the emergency department.…”
Section: Contextual Influencesmentioning
confidence: 99%
“…Previous studies on pediatric pain assessment in the ED setting have primarily measured acute pain as a chief complaint (Alexander & Manno, 2003;Chisholm et al, 2008;Crocker, Higginbotham, King, Taylor, & Milling, 2011;Fry et al, 1999;Garra et al, 2009;Gourde & Damian, 2012;Johnston et al, 1998;Kelly, Powell, & Williams, 2002;Maciocia et al, 2003;McConahay, Bryson, & Bulloch, 2006;O'Donnell, Ferguson, & Bettie, 2002;Probst et al, 2005;Rajasagaram, Taylor, Braitberg, Pearsell, & Capp, 2009;Russo, 2010;Santervas, et al, 2010;Shavit, Kofman, Leder, Hod, & Kozer, 2009;Strout & Baumann, 2011). The most common method to identify pain assessment practices in the emergency department has been through survey and retrospective chart review (Alexander & Manno, 2003;Jadav, Lloyd, McLauchlan, & Hayes, 2009;Kaplan, Sison, & Platt, 2008;Kleiber, Jennisen, McCarthy, Ansley, 2011;May et al, 2009;Porter & Chapman, 2004;Probst et al, 2005;Santervas et al, 2010;Strout & Baumann, 2011); however, healthcare providers' have been found to report better pain assessment practices on surveys then when compared to actual practice (Read, 1994;Twycross, 2007b;Twycross, 2008).…”
Section: Pediatric Pain Assessment In the Emergency Departmentmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 There is ample evidence that analgesia is underused in the ED setting. [7][8][9][10] Furthermore, untreated pain in childhood has been reported to lead to slower healing [11][12][13][14] and long-term issues, such as anxiety, needle phobia, 15 hyperesthesia, 13 and fear of medical care. 16 Despite general acceptance that children experience significant pain-related urethral procedures, [17][18][19] suboptimal analgesia is particularly prevalent in children undergoing UC, with analgesic rates ranging from 0% 6 to 2%.…”
Section: What This Study Addsmentioning
confidence: 99%